The Role of Perceived Organizational Support (POS) and Employee Satisfaction to Enhance Employee Engagement: Do Gender and Tenure Matter? - Eviana, Nova (Jurnal Manajemen Bisnis, 2024)
Research aims: The research investigated the conjecture that employee engagement is notably intensified in the presence of perceived organizational support (POS) and employee satisfaction. Additionally, the study explored the discrete impacts of the interconnections between these variables, considering gender and employee tenure. Design/Methodology/Approach: This study employed primary quantitative research methods through cross-sectional surveys. The hypotheses were tested using SEM-PLS with the assistance of Smart PLS.Research findings: The findings unveiled that POS indirectly influences employee engagement through its effect on employee satisfaction. Furthermore, employee satisfaction directly and positively contributes to heightened employee engagement. Neither gender nor tenure exhibits identifiable effects on the correlations between the constructs. It is ascertained that POS holds a higher degree of significance in cultivating employee engagement.Theoretical Contribution/Originality: The study empirically confirmed the enhanced employee engagement through POS and employee satisfaction, elucidating the mediating role of satisfaction, highlighting the significance of POS, and offering actionable managerial insights for human resource strategies.Practitioners/Policy Implications: It is recommended that managerial efforts be directed toward formulating human resource strategies that amplify POS.Research Limitations/Implications: Limited number of respondents due to the period of COVID-19 recovery.